Intelligent Carom Billiards Assistive System for automatic solution path generation and actual path prediction with principal component analysis-based ball motion detection. (29th August 2022) - Park, Jung-kil; Park, Jaebyung
This article proposes an Intelligent Carom Billiards Assistive System for a novice at Carom Billiards. Since a novice player is very difficult to find the solution paths of the cue ball, the ICBAS automatically calculates the solution paths for given ball configuration which is detected by a monocular vision and displays them in a guidance monitor. For rapid and systematically calculating the solution paths, the five and half system that is the most representative method in the field of billiard is implemented. In addition, the paths of the cue ball changed by the direction of the cue stick are predicted in real time and projected onto the pool table bed. By comparing the solution paths of the cue ball with the projected paths, a player can hit the cue ball easily and successfully. For automatically providing the solution paths and the predicted paths during billiard game, the ball movement is detected by the principal component analysis under linear motion constraints robustly against image noise, occlusion, and so on. Whenever all of the balls stop, both paths are newly calculated and provided for a player. For verifying the feasibility of the proposed Intelligent Carom Billiards Assistive System, the experiments are conducted with the real pool table.